Remedies for Wrongful Convictions in India: Examining the Factors Contributing to Wrongful Convictions and Proposed Remedies in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India recognises that wrongful imprisonment is among the worst forms of injustice. The authorprovides an analysis of the factors that contribute to this injustice in India, including the nature of ourjudicial system and the evolution of the legislation on this topic as a result of several cases. It drawsattention to the injustices of our court system and the misery of those who were wrongfully convicted. Atthe conclusion of the article, the author warns us about the urgent need for judicial adjustments andreiterates the importance of the State protecting people' rights. Possible remedies under public law,private law, and criminal law were also discussed. Eyewitness confusion is the leading cause of wrongfulconvictions, followed by faulty forensics, false confessions, official misconduct, the use of informants,and ineffective defence. These factors contribute to an alarmingly high rate of wrongfully convictedindividuals.The author of this paper discusses India's legal recourse for erroneous convictions.